ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TAX COMPLIANCE WAJIB PAJAK BADAN PADA PERUSAHAAN JASA DI KOTA PEKALONGAN - SE, M.Si, Sobrotul Imtikhanah; SE, M.Si, Tutut Dwi Andayani; SE, Farah Baety (Majalah Neraca, 2015)
This research was conducted to investigate corporate tax compliance behavior, especially service company in Pekalongan city. Research design was a replication of Laksono research (2011) with the respondents location as a difference. The respondents of the research were tax professionals who have at least 1 year experience as tax professional in the service company and ever filled SPT form. Seventy seven tax professionals were almost served as finance staff of 77 corporates participated in this research. The data was analysed using SPSS version 16. This research used tax professional attitude, tax professional subjective norm, tax professional perceived behavioral control, corporate financial condition, corporate facilities, and corporate organizational as independent variables and corporate tax compliance as dependent variable. The findings of this research showed that : (1) tax professional attitude does not affect on corporate tax compliance; (2) tax professional subjective norm affect on corporate tax compliance; (3) tax professional perceived behavioral control affect on corporate tax compliance; (4) corporate financial condition does not affect on corporate tax compliance; (5) corporate facilities does not affect on corporate tax compliance; and (6) corporate organizational affect on corporate tax compliance. Keywords: tax professional attitude, tax professional subjective norm, tax professional perceived behavioral control, corporate financial condition, corporate facilities, corporate organizational, and tax compliance